MEDIA EDUCATION FOR FUTURE MEDIA PROFESSIONALS: DESIGNING AND IMPLEMENTING A TRAINING PROGRAMME - Olena Yevtushenko; Tetiana Kovalova (Novìtnâ Osvìta, 2019)
The paper presents the experience of the media education project for journalism students at Sumy State University. The workshops dealt with different media categories (media agencies, media technologies, media languages, media audience, media representations) and necessary components of communicative competence (technical information competence, information competence, social information competence, technical media competence, media competence, social media competence). During October 2017 - January 2018, five workshops and seminars were held. For each activity, input and output survey was conducted to assess the extent to which the level of knowledge and skills of the participants on a particular topic increased, as well as how the participants evaluated the project. On average, 32 people took part in each workshop, 78% of them filled in the questionnaires (in total 140 input and 112 output questionnaires were analysed). The results showed that despite the high level of initial knowledge of the participants, the training course contributed to their understanding of certain media categories and other specific issues. The participants also pointed out the importance and relevance of the information for their professional activity. The survey of 29 regular project participants and 27 professional journalists working in the mass media of Sumy Region was conducted to assess the project effectiveness. The participants highly assessed their knowledge of media literacy. The students’ results were similar to those of professionals’ (in the assessment of knowledge acquired, understanding the notion of media literacy, determining the main tasks of media education and the most effective ways of acquiring media competences). However, the students evaluated their analytical skills lower and rarely applied them. Further workshops will be aimed at dealing with this issue. The analysis of survey results proves the efficiency of the combination of formal and non-formal teaching methods for journalism students. It is important both for the training participants and the universities as they have become more competitive and able to face the challenges of academic education nowadays. The experience described can be implemented by other academic institutions to improve the quality of journalism education in Ukraine.